Polyamine sulfur conjugates: a paradigmn for selective drug delivery to cancer cells via polyamine transport system - Abdul Ghani, Radiah; Sahabudin, Adzly Hairee; How, Fiona Ni Foong; Ikmal Hisham, Ahmad Irfan (2018)
During these modern times, numerous types of diseases have been spread and cause death to humanity. One of the diseases that cause a major threat to humanity is cancer. According to the World Health Organization (2017), in 2015, cancer had caused 8.8 million deaths globally. The most lethal which is lung cancer (along with trachea and bronchus cancers) had caused 1.7 million deaths which is the 5th most caused death worldwide. Various new methods and drugs on ways to prevent as well as to cure, treat and reduce the effects of cancer have been discovered and researched. However, most of the drugs, artificial and natural, have been known to cause one or several side effects towards the patient while some may cause the cancer patient to undergo painful treatments.Despite most anticancer drugs possess potent cell killing activity in vitro studies; the selective delivery of drugs to cancer cells is thus far becomes a major challenge to oncology. The non-specific actions of drugs on healthy cells cause many restrictions in clinical use due to their systemic toxicity. In response to this matter, specific targeting of anticancer drugs towards cancer cells can be achieved by attaching them to a molecule that is transported into cancer cells via a selective transport system. One strategy to achieve this selective delivery is by exploiting specific transport mechanisms such as the polyamine transport system (PTS). The PTS is an energy-dependent machinery frequently over activated in cancer cells with a high demand for polyamines. Cancer cells differ from healthy cells by the amount of polyamine presents. In cancer cells, the amount of polyamine is higher as it needs more polyamine to grow. By using the PTS, it is hoped that the anti-cancer compound can be transferred to the targeted cells and minimize the harm to healthy cells.